Pheochromocytoma. - Castro, J M; Garcia, J P (Acta Médica Portuguesa, 1994)
The authors present the case of a 51 year old woman with severe arterial hypertension with parixisms, without medical control. The clinical, laboratory and imagiological investigation showed a pheochromocytoma at the right adrenal gland. The patient was submitted to surgery with success. Specific aspects of differential diagnosis are discussed and a review of the more relevant features of clinical diagnosis, pre-operative preparation and surgical technique are presented.